An investigation reliability of existing reinforcement concrete structure (beam) using non destructive test at Kolej Komuniti Jasin [electronic resource] - Norhafizan Majid, 1980-; Izni Syahrizal Ibrahim, supervisor; Fakulti Kejuruteraan Awam (2013)
Thesis (Sarjana Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2013